a)(2+√3)²+(2-√3)²
b)(√3+2√2)²+(3√3-√2)²-(√3+√2)(√3-√2)
c)(2√3-1)²+(√3+2)²-(√3-5)(√3+5)
Ajutati-ma va rog
Răspunsuri la întrebare
Răspuns de
1
a).(2+√3)²+(2-√3)²=4+4√3+3+4-4√3+3=14
b).(√3+2√2)²+(3√3-√2)²-(√3+√2)(√3-√2)=3+4√6+8+27-6√6+2-(3-2)=3+4√6+8+27-6√6+2-3+2=39-2√6
c).(2√3-1)²+(√3+2)²-(√3-5)(√3+5)=12-4√3+1+3+4√3+4-(3-25)=12-4√3+1+3+4√3+4-3+25=42
b).(√3+2√2)²+(3√3-√2)²-(√3+√2)(√3-√2)=3+4√6+8+27-6√6+2-(3-2)=3+4√6+8+27-6√6+2-3+2=39-2√6
c).(2√3-1)²+(√3+2)²-(√3-5)(√3+5)=12-4√3+1+3+4√3+4-(3-25)=12-4√3+1+3+4√3+4-3+25=42
Răspuns de
2
a)(2+√3)²+(2-√3)²
=4+4√3+3+4-4√3+3
=14
b)(√3+2√2)²+(3√3-√2)²-(√3+√2)(√3-√2)
=3+4√6+8+27-6√6+2-(3-2)
=3+4√6+8+27-6√6+2-3+2
=39-2√6
c)(2√3-1)²+(√3+2)²-(√3-5)(√3+5)
=12-4√3+1+3+4√3+4-(3-25)
=12-4√3+1+3+4√3+4-3+25
=42
=4+4√3+3+4-4√3+3
=14
b)(√3+2√2)²+(3√3-√2)²-(√3+√2)(√3-√2)
=3+4√6+8+27-6√6+2-(3-2)
=3+4√6+8+27-6√6+2-3+2
=39-2√6
c)(2√3-1)²+(√3+2)²-(√3-5)(√3+5)
=12-4√3+1+3+4√3+4-(3-25)
=12-4√3+1+3+4√3+4-3+25
=42
Utilizator anonim:
cu placere:)\
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Chimie,
10 ani în urmă
Matematică,
10 ani în urmă
Chimie,
10 ani în urmă